2022
DOI: 10.1186/s10086-022-02015-8
|View full text |Cite
|
Sign up to set email alerts
|

A one-dimensional elasto-viscoplastic model coupled to damage for the description of creep in wooden materials

Abstract: This work focuses on the development of a model for the description of the tertiary creep phenomenon in wooden materials. We stared from an extended standard solid body model capable of best describing primary and secondary creeps. We then modify this model by introducing a damage variable to explain and model the rapid growth of viscoplastic strain during tertiary creep. We obtain a model comprising a reduced number of parameters (05) all physically interpretable; which can be easily determined from the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Wood can undergo complex viscoelastic and viscoplastic deformation [10,11]. Pang et al [12] demonstrated strain-rate dependencies of Beech wood with compressive yield and ultimate stresses increased by around 250% when comparing quasi-static and transient-dynamic loads with strain rates of up to 2000 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Wood can undergo complex viscoelastic and viscoplastic deformation [10,11]. Pang et al [12] demonstrated strain-rate dependencies of Beech wood with compressive yield and ultimate stresses increased by around 250% when comparing quasi-static and transient-dynamic loads with strain rates of up to 2000 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…10 Many attempts have been curried out to ascribe these properties to the micro-structure behaviour. Foth et al 11 introduced a description of the tertiary creep phenomenon in wooden materials using the experimental results of creep-rupture tests under creep stress. Two-step extrusion process, and mechanical properties such as strength, elastic modulus and Poisson's ratio of Wood Plastic Composite were investigated in.…”
Section: Introductionmentioning
confidence: 99%